Improving pregnancy care during the COVID-19 pandemic for pregnant women as vulnerable groups through assistance at the primary health care facility - Muhamad Jauhar; Kurniati Puji Lestari (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2021)
Since it was found in December 2019, the novel Coronavirus Disease 2019 (COVID-19) has spread from Wuhan, China, to many other countries. A rapid increase of newly found cases was observed, and finally, in March 2020, the World Health Organization declared that Coronavirus Disease 2019 (COVID-19) is a global pandemic. As one of the vulnerable groups, pregnant women need to avoid COVID-19 transmission and maintain pregnancy health during the pandemic. This study aimed to improve pregnant women's self-management during the COVID-19 pandemic in the working area of the Padangsari Primary Health Care Services, Semarang City. The research method used an experimental design with a pre-posttest without a control group. A Smartphone application, namely